HOMONYMS THAT DIFFER IN STRESS IN ENGLISH AND UZBEK LANGUAGES - Ro’zimboyeva Sitora Nurmamatovna (American Journals Publishing, 2023)
When it comes to homonyms that differ in accent, he is relevant for both languages. English and Uzbek languages in this article homonyms that differ in texts and speech, their analysis it is about making and differentiating.
Keywords: homonyms, words, texts, word groups, syllables, additions, accents and sounds.